تكنولوجيا المعلومات ودورها في تعزيز رأس المال البشري باعتباره موردا استراتيجيا لتحقيق الميزة التنافسية - غريب، منية Gharib, Muniah (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2015)
Most organizations adopt at the present time the principle of interest in human beings as one of the powerful effects that give them a competitive advantage, especially with the entry of the twenty-first century, Especially with the entry of the twenty-first century, which is based on the knowledge economy, and that the productivity of human capital is a key test for the province to any successful organization in the market and the basis of any successful economy in the world. All this makes it imperative to have adequate, true and accurate information about the human element, so it becomes possible to increase his effectiveness and development, which earns organizations a competitive advantage in the market place.
تتبني أغلب المنظمات في وقتنا الحالي مبدأ الاهتمام بالبشر كأحد المؤثرات القوية التي تعطيها ميزة تنافسية، خاصة مع دخول القرن الواحد والعشرين والذي يرتكز على اقتصاد المعرفة، ويعتبر أن إنتاجية رأس المال البشرى هي المحك الرئيس للمحافظة على أي منظمة ناجحة في السوق وأساس أي اقتصاد ناجح في العالم. حيث أصبحت القوة الدافعة لتلك المنظمات هي الأفراد ذوي المعرفة، والذكاء، والمهارات التي تتلاءم مع متطلبات القرن الحالي. كل هذا يحتم ضرورة توافر معلومات كافية، صحيحة ودقيقة عن العنصر البشرى حتى يصبح من الممكن زيادة فاعليته وتطويره مما يكسب المنظمات ميزة تنافسية في السوق.
Keywords: الاقتصاديات المعرفية -- تكنولوجيا المعلومات -- رأس المال البشري -- الموارد الاستراتيجية -- الميزة التنافسية